Infrastructural Ecology: Embedding Resilience in Public Works. (January 2019) - Brown, Hillary
The destabilization of earth's climate—manifest today in rising sea levels, more frequent droughts, deluges, and rising temperatures—demands expansive thinking in our infrastructural investments. Such volatility imperils coastal and riverine populations, degrades agriculture, and fosters water insecurity. We require innovative, multidimensional solutions to these public works challenges. Infrastructural ecology is a planning paradigm that emulates the closed-loop, sharing logic of natural ecosystems. It suggests that features of our power, water, sanitation, transport, and food systems may be strategically combined, collocated, or otherwise linked for mutual benefit. Such interconnected systems then can cascade (pass along) waste energy or water and nutrients for another's reuse, arrangements that can reduce pollution and greenhouse gas emissions, while lowering demand for new resource inputs. Innovative examples from both industrialized as well as developing nations illustrate the efficacy of these strategies. The exemplary projects described here include smart coastal solutions, water-wise innovations, and coping strategies for warming cities.